الضمانات السياسية والإجتماعية للحقوق والحريات السياسية - العلوان، علي يوسف محمد (الجمعية العلمية للبحوث والدراسات الاستراتيجية, 2016)
In many of countries the Constitutional documents included a lot of provisions which decide to protect human rights and freedoms, notably political rights and freedoms. However, the practice is clearly confirmed that the protection of these rights and freedoms is not only achieved it in constitutional documents, but need to provide guarantees to adequate sponsorship, these documents from the rights and freedoms determined by them, and strengthen political steps and practical measures Lead to overcome any obstacles For individuals to get their rights and freedoms. Here show the importance of political and social safeguards, which sometimes be more effective Especially if guarantees seemed as a legal construction in goal and the way. Among the most prominent of these parliamentary oversight safeguards And control public opinion and the democratic system, Here we must emphasize the essential and faith is the extent and effectiveness of individuals effectively, Those guarantees and stick to it and care for it. them because of their remarkable and effective impact on political activity and particularly in democratic societies, which leads to the result to reply violations of rights and political freedoms, and that those political guarantees are indispensable because it is the case of pressure on governments to respect the rights and freedoms in general, reported violations of rights and political freedoms in particular.
لقد تضمنت الوثائق الدستورية في العديد من الدول نصوصا مختلفة تقرر حماية حقوق الإنسان وحرياته ومن أبرزها الحقوق والحريات السياسية، إلا أن الواقع العملي أكد بشكل واضح أن حماية تلك الحقوق والحريات لا يتحقق فقط بالنص عليها في الوثائق الدستورية بل لابد من توافر الضمانات الكافية لكفالة ما تقرره لهم هذه الوثائق من حقوق وحريات وتعزيزها بخطوات سياسية وتدابير عملية تؤدي إلى تجاوز أي معيقات لممارسة الأفراد لحقوقهم وحرياتهم، وإلا ستبقى أي نصوص وضعية تشكل ضمانات نسبية لا يمكن أن تكون لوحدها محققة للحماية الفاعلة. وهنا تظهر أهمية الضمانات السياسية والاجتماعية التي تكون في بعض الأحيان أكثر فاعلية خصوصا إذا ما حادت الضمانات ذات البناء القانوني عن هدفها وطريقها، ومن أبرز هذه الضمانات الرقابة البرلمانية ورقابة الرأي العام والنظام الديمقراطي، وهنا لابد من التأكيد على أمر جوهري وهو مدى إيمان الأفراد بنجاعة وفاعلية تلك الضمانات والتمسك بها والحرص عليها لما لها من تأثير ملحوظ وفعال على النشاط السياسي وبشكل خاص في المجتمعات الديمقراطية مما يؤدي بالنتيجة إلى رد الانتهاكات عن الحقوق والحريات السياسية، كما أن تلك الضمانات السياسية لا غنى عنها لأنها تشكل حالة ضغط على الحكومات لحملها على احترام الحقوق والحريات بشكل عام، ورد الانتهاكات عن الحقوق والحريات السياسية بشكل خاص.
Keywords: حقوق الإنسان -- الحريات السياسية -- الحماية -- الدساتير -- دول العالم